Formation of the transition zone by Mks5/Rpgrip1L establishes a ciliary zone of exclusion (CIZE) that compartmentalises ciliary signalling proteins and controls PIP2 ciliary abundance. (21st September 2015) - Jensen, Victor L; Li, Chunmei; Bowie, Rachel V; Clarke, Lara; Mohan, Swetha; Blacque, Oliver E; Leroux, Michel R
Abstract Cilia are thought to harbour a membrane diffusion barrier within their transition zone (TZ) that compartmentalises signalling proteins. How this "ciliary gate" assembles and functions remains largely unknown. Contrary to current models, we present evidence that Caenorhabditis elegans MKS‐5 (orthologue of mammalian Mks5/Rpgrip1L/Nphp8 and Rpgrip1) may not be a simple structural scaffold for anchoring > 10 different proteins at the TZ, but instead, functions as an assembly factor. This activity is needed to form TZ ultrastructure, which comprises Y‐shaped axoneme‐to‐membrane connectors. Coiled‐coil and C2 domains within MKS‐5 enable TZ localisation and functional interactions with two TZ modules, consisting of Meckel syndrome (MKS) and nephronophthisis (NPHP) proteins. Discrete roles for these modules at basal body‐associated transition fibres and TZ explain their redundant functions in making essential membrane connections and thus sealing the ciliary compartment. Furthermore, MKS‐5 establishes a ciliary zone of exclusion (CIZE) at the TZ that confines signalling proteins, including GPCRs and NPHP‐2/inversin, to distal ciliary subdomains. The TZ/CIZE, potentially acting as a lipid gate, limits the abundance of the phosphoinositide PIP2 within cilia and is required for cell signalling. Together, our findings suggest a new model for Mks5/Rpgrip1L in TZ assembly and function that is essential for establishing the ciliary signalling compartment.